A review of fluoroscopy guided percutaneous transpedicular spinal biopsies at Charlotte Maxeke Johannesburg Academic Hospital - Bhikha, Shivam (University of the Witwatersrand, Johannesburg, 2023)
Background: When a suspicious spine lesion is identified, an accurate diagnosis based on tissue biopsy is required in order to direct towards the correct treatment protocol. Several studies have demonstrated that the percutaneous fluoroscopy guided biopsy of a vertebral lesion is a safe, effective and accurate diagnostic tool and is preferred over open techniques when possible. Thereby obviating the need for major surgery and expediting appropriate management of patients. Fluoroscopy guided percutaneous transpedicular vertebral biopsies have a varying complication rate from 0 to 10%. Study Aim: The aim of the study was to review percutaneous fluoroscopy guided transpedicular spinal biopsies at Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) over a 6-year period. Methodology: The research design was a retrospective study of patients who underwent a percutaneous transpedicular spinal biopsy under fluoroscopy guidance. Research site was the Charlotte Maxeke Johannesburg Academic Hospital (CMJAH). The time period for the study covered a span of six years i.e. from 1st of January 2016 to the 31st of December 2021. The CMJAH spine theatre registry and hospital records system were used as the source for data collection. Statistical analysis was conducted to determine the effectiveness of the transpedicular spinal biopsy, compare spinal pathology amongst age and gender and to identify any complications. Results: The study analysed 180 biopsies, with 120 yielding a positive result (66.67%). Of these 8.9% were pyogenic infection, 18.4% neoplasm, 36.7% Tuberculosis and 2.7% other. There were 75 males and 105 females with an age range between 9 and 86 years and mean age of 43.44. Comparing age and gender distribution showed no statistical significance (p = 0.778). Comparing biopsy result and gender showed no statistical significant relationship (p = 0.970). Comparison of biopsy result with age showed no statistical significant association (p = 0,545). Four complications were identified (2.22%). Conclusion: The study showed that fluoroscopy guided percutaneous transpedicular biopsy is an effective modality in obtaining thoracic and lumbar vertebrae specimens in all age groups for a wide spectrum of spinal pathological lesions. The study also proves that it is a safe procedure with no long term complications.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Medicine, to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Spine lesion; Transpedicular; Percutaneous biopsy; Fluoroscopy guided; Spinal Tuberculosis; Spinal Metastases; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education